INVESTIGATION OF STUCK PIPE RELEASE THE DRILL STRING SHOCK DEVICE - Левчук, Катерина Григорівна; Цідило, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Аnalyzes the dynamics of stuck drill string section (DS) using shock device, which based on static solution of elasticity and plane wave method. The authors mathematically modeled oscillatory motion of the drill pipe sections, set the speed and time of the meeting configurations DS, built diagram shock wave forces on a meeting within sections and place stuck. The creators obtained analytical formulas for assessing the dynamic characteristics of impact, the speed of release of stuck DS and its movement during the strike helped to create numerical algorithm for solving nonlinear equations dynamically using computer packages symbolic mathematics. The researchers numerical study conducted by the example given layout DS also. For this drill string length calculated blow-coefficient update attitude, accumulated energy due to elastic deformation DS, energy, lost to strike itself to loosening-kick, striking the momentum built at the site of a plane wave stuck pipe.